Understanding the association between skin involvement and joint activity in patients with psoriatic arthritis: experience from the Corrona Registry - Philip J Mease; Jeffrey D Greenberg; Carol J Etzel; William J Huster; Talia M Muram; April W Armstrong; Jeffrey R Lisse; Sabrina Rebello; Rhiannon Dodge; Mwangi James Murage; William N Malatestinic (RMD Open)
Objective To compare the characteristics of patients with psoriatic arthritis among patient groups stratified by degree of skin and joint involvement, and to evaluate the relationship between skin severity and joint activity.Methods Body surface area (BSA) and Clinical Disease Activity Index (CDAI) at enrolment were analysed. Patient characteristics were stratified by skin severity and joint activity. Baseline patient characteristics, clinical and disease characteristics and patient-reported outcomes were compared. The strength of the relationship of skin severity and joint activity was evaluated using methods for categorical variables (χ2 test, Cramer’s V) and continuous variables (linear regression).Results 1542 adult patients in the Corrona Psoriatic Arthritis/Spondyloarthritis Registry enrolled between 21 May 2013 and 20 September 2016 were analysed. Most patients in the BSA >3%/CDAI moderate/high subgroup had worse clinical and patient-reported outcomes. A significant (p<0.001) modest association (Cramer’s V=0.1639) between skin severity and joint activity was observed among all patients at enrolment. Patients with higher skin severity were two times more likely to have higher joint involvement (OR 2.27, 95% CI 1.71 to 3.01). A significant linear relationship between CDAI and BSA was observed. Effect modification showed this linear relationship was modified by age, gender, insurance, work status, current therapy, Health Assessment Questionnaire, Nail visual analogue scale, minimal disease activity, dactylitis count, patient-reported pain and fatigue.Conclusion Skin severity is modestly correlated with joint activity, and patients with higher skin severity are two times more likely to have increased joint involvement. Clinicians need to address both skin severity and joint activity in treatment decisions.